Some COVID-19 relevant considerations in the elderly - Ana Esther Despaigne Biset; Idalmis Vallejo Santiago; Leysa Margarita Gòmez; Caridad Tamayo Reus; Sandra Laurencio Vallina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
COVID-19 can affect anyone regardless of age, sex or race; but numerous studies have focused on characterizing its heterogeneity in demographic terms, with clear evidence of high mortality in men and older adults. The objective of this work is to make some considerations about covid-19 and its impact on the elderly. A bibliographic search was carried out taking into account some relevant considerations of the disease, present in the elderly, such as their susceptibility to covid-19, clinical elements, complications and treatment. It was possible to verify, according to the analyzed publications, that the elderly is considered the most susceptible to COVID-19, morbidity and mortality increases with age and due to the lower immune defense response in the presence of comorbidities; the symptoms are highly variable and atypical with the appearance of multiple extrapulmonary complications and prevention, is the most effective course of action. Older adults continue to be considered a vulnerable population and prevention and timely diagnosis are required in order to minimize damage to health.